Adaptive Reuse Practice in The Mosque of Sang Cipta Rasa Cirebon, West Java (Actualizing Religious Tourism) - Ashri Prawesthi D; Adrianto Ibnu; Ega Adhisty; Tea Gita (International Journal of Glocal Tourism, 2021)
Purpose: The study aims to identify the existing practice of adaptive reuse of The Mosque of Sang Cipta Rasa Cirebon, West Java, Indonesia, to actualize the destination of religious tourism. Research methods: The Mosque of Sang Cipta Rasa Mosque as a case study was undertaken with the following instruments: interviews with the Building Authorities, on-site observations of the building conditions, literature search on the previous conservation reports. Findings: The findings suggest improvements on conservation practices by highlighting the discrepancies of the existing heritage building control procedures and requirements. It facilitates the local building authorities to formulate new systematic and transparent conservation guidelines. Implications: An Adaptive-Reuse is one of the ways to preserve the heritage building. The government can be implied this model as a policy to preserve their heritage buildings.